Efektivitas Campuran Limbah Bata Ringan Terhadap Peningkatan Kuat Tekan Bebas Pada Tanah Berbutir Halus - Hamdan Kadir; Wudi Darul Putra; Agil Nung; Akmal Fais (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
Fine-grained soils generally possess low bearing capacity, high plasticity, and low unconfined compressive strength, requiring stabilization prior to their use as subgrade materials in construction works. One alternative method is the utilization of construction waste in the form of lightweight brick waste or Autoclaved Aerated Concrete (AAC), which contains active silica and has the potential to improve soil strength. This study aims to evaluate the effectiveness of AAC waste as a stabilization material for fine-grained soils in improving the Unconfined Compressive Strength (UCS). The soil samples were compacted using a standard compaction method to achieve optimum density conditions. AAC waste was added at variations of 0%, 2%, 4%, 6%, and 8% of the dry weight of soil. The soil-AAC mixtures were then molded and tested for UCS under both remolded and unremolded conditions. In addition, UCS tests were conducted with curing periods ranging from 0 to 3 days to analyze the effect of early curing on the strength development of stabilized soil. The results indicated that the addition of AAC waste increased the UCS value up to an optimum content of 6%. At this percentage and a curing period of 3 days, the soil achieved an unconfined compressive strength (qu) of 2.518 kg/cm², an undrained cohesion (Cu) of 1.259 kg/cm², and a soil sensitivity (St) value of 1.747. Overall, AAC waste has significant potential as an environmentally friendly alternative material for the stabilization of fine-grained soils in geotechnical engineering applications.